Deaf side story : deaf Sharks, hearing Jets, and a classic American musical - Rigney, Mark (Gallaudet University Press, 2003)
"The 1957 classic American musical West Side Story has been staged by countless community and school theater groups, but none more ambitiously than the 2000 production by MacMurray College, a small school in Jacksonville, Illinois. Diane Brewer, the new drama head at the college, determined to add an extra element to the usual demands of putting on a show by having deaf students perform half of the parts. Deaf Side Story presents a fascinating narrative of Brewer and the cast's efforts to mount this challenging play."--Jacket.